Implementation of ISO 31000-Based Risk Management in Enhancing the Sustainability of Digital Business Platforms in Indonesia - Josephin Cornellius; Rhian Indradewa; Muhammad Dhafi Iskandar; Unggul Kustiawan (Yayasan Riset dan Pengembangan Intelektual, 2026)
The rapid growth of digital businesses in Indonesia presents significant opportunities along with increasingly complex risks, particularly in technological, operational, and reputational aspects. This study aims to analyze the implementation of ISO 31000-based risk management in enhancing the sustainability of digital businesses. The research employs a qualitative approach using a literature review method by analyzing various relevant scientific journals. The findings indicate that technological and operational risks are the most dominant, categorized as high to extreme risks. The implementation of ISO 31000 risk management, which includes risk identification, analysis, evaluation, and mitigation, has proven effective in improving operational stability, reducing potential losses, and increasing customer trust. Furthermore, this study highlights that risk mitigation strategies must be adapted to industry characteristics to achieve optimal effectiveness. Therefore, risk management becomes a key factor in ensuring the sustainability of digital businesses in the era of technological transformation.